Intervention in the Interest of Deprived Elderly People - Norbert Vajda (Universitas Ahmad Dahlan, 2015)
AbstractBeside we have to have adequate answers for our material needs we must have active Â relationships with our social environment as well. People living in segregated circumstancesÂ have limited access to the rest of the society, but elderly people of these fields can be mentallyÂ separated from their own communities too, according to recent research results in Hungary.In every society of the world, external intervention for inhabitants must be based on relevantÂ information. This has got two main resources: the first one is the theoretical framework ofÂ group processes; the second is the practical knowledge of the special territory where theÂ programs can be implemented. This paper has got three main chapters. From theÂ â€œIntroductionâ€ the Reader will understand a special element of social inequalities, when weÂ are going to concentrate on the determinant role of residential segregation. In the secondchapter we will deal with the disintegration process and the decaying solidarity level of Â small communities, which has a major impact on elderly care. After we introduced the details Â of this question, we will provide a good example for intervention in the interest of peopleÂ living in smaller settlements with dementia. In the â€œConclusionâ€we will summarize theÂ main points, with onwards thoughts about further development.Keywords: elderly, deprived groups, social intervention, and dementia